Exploring Problem-Based Learning within Physical Education in Indonesia: A Content Analysis - Rozi, Fatkhur; Wulansari, Dasih Ayu; Daryanto, Daryanto; Sukmana, Muhammad Endra; Syahputri, Aulia Maris; Hasan, Siti Nur Syahiirah; Hasan, Siti Nur Syafiqah; Ramadhan, Fathurrohman Syahrul; Zuhri, Syarifuddin (Berkala Ilmiah Pendidikan, 2025)
The Problem-Based Learning (PBL) model plays a crucial role in developing critical thinking and problem-solving skills, which are essential for 21st-century education. This study aims to analyze the content of field research focusing on the application of the PBL model in physical education (PE) in Indonesia. Although numerous articles have been published on PBL, few have conducted content analyses on this topic. Therefore, this study explores the implementation of PBL in Indonesian physical education using a content analysis approach. The research employed a content analysis design, with the primary data source consisting of articles from SINTA-indexed PE journals. A total of 13 articles published between 2006 and 2023 met the criteria for analysis. The findings highlight significant opportunities for further PBL research in Indonesian PE, particularly using qualitative methods. Notably, there is a lack of studies involving grade 9 or 12 students. Most existing research focuses on learning outcomes, uses a variety of intervention types, and frequently relies on questionnaires and test sheets. Additionally, some quasi-experimental studies were found to use inappropriate data analysis techniques. This review provides critical baseline evidence to guide future research and pedagogical innovation in PE by identifying current gaps and methodological limitations in how PBL is applied and studied in Indonesia.